The Classification of “Program Sembako” recipients in Payobasung West Sumatra based on the K-nearest neighbors classifier - HAZMIRA YOZZA; NINDI MAULA AZIZAH; LYRA YULIANTI; IZZATI RAHMI (Universitas Syiah Kuala, 2023)
The